2016
DOI: 10.1016/j.contraception.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Emergency contraception: A multispecialty survey of clinician knowledge and practices

Abstract: Objectives To assess knowledge and provision of emergency contraception (EC), particularly the most effective methods. Study Design A web-based survey was distributed to a cross-sectional convenience sample of healthcare providers across specialties treating reproductive-aged women. The survey was sent to 3,260 practicing physicians and advanced practice clinicians in 14 academic centers between February 2013 and April 2014. We analyzed responses by provider specialty using multivariable logistic regression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 22 publications
1
40
1
Order By: Relevance
“…Although pharmacists in both components of our study had relatively limited knowledge of the IUD as EC, a finding that is consistent with other studies of health professionals in North America [25], our participants expressed considerable interest in participating in such an initiative. Importantly, pharmacists saw themselves as being well-positioned to offer these types of referrals and identified that this type of program would meet a demonstrable need.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Although pharmacists in both components of our study had relatively limited knowledge of the IUD as EC, a finding that is consistent with other studies of health professionals in North America [25], our participants expressed considerable interest in participating in such an initiative. Importantly, pharmacists saw themselves as being well-positioned to offer these types of referrals and identified that this type of program would meet a demonstrable need.…”
Section: Discussionsupporting
confidence: 72%
“…Further, in recent years there has been a plethora of efforts in North America to expand access to long-acting, reversible contraception [21][22][23]. Misinformation among providers, a dearth of trained providers, high up-front costs, and lack of awareness among women have limited the availability and accessibility of IUDs, both as ongoing methods of contraception and as EC [24][25][26]. Yet research also suggests that when women are informed about the IUD as EC, demand increases [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published data by Batur et al demonstrates near universal awareness of LNG ECP as an emergency contraception method amongst providers across specialties caring for women of reproductive age, while familiarity with UPA is at 50% for reproductive health providers and 15% for emergency medicine [8]. Increased education of clinicians, pharmacists and patients regarding the range of ECPs available and the important differences between them may assist in increasing demand for UPA, as well as motivation for prescribers to partner with pharmacies in navigating distribution and other systems-based barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Although UPA is preferable in most situations because it is more effective than LNG (Glasier et al, 2010), UPA can be difficult to access. UPA EC is a prescription-only product, and awareness and provision of this option are low among healthcare providers (Batur et al, 2016). In addition, availability of UPA in pharmacies may be extremely limited: in a recent study of all pharmacies in Hawaii, only 2.6% had UPA immediately available, while 82.4% had LNG EC in stock (Bullock et al, 2015).…”
Section: Introductionmentioning
confidence: 99%